ANALISIS DAMPAK LALAULINTAS ON-OFF RAMP JATIKARYA TERHADAP JALAN TRANSYOGI , CIBUBUR - Darmadi; AR Indra Tjahjani (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2019)
The Cimanggis - Cibitung toll road is part of the development of the Jakarta city ring toll road in accordance with the Government of the Republic of Indonesia program in overcoming traffic congestion in Jabotebek. Cimanggis - Cibitung Toll Road is the second Jakarta toll ring road from Cibitung - Cimanggis - Ciputat - Balaraja. In this segment, Cimanggis - Cibubur has an exit from the Jatikarya toll road, which meets the National Transyogi road in the city of Jatikarya. This Jatikarya Exit toll road will affect traffic behavior on the National Transyogi road, both congestion and vehicle speed. The study of the effect of Jatikarya toll exit is aimed at evaluating the speed, density, traffic volume, V / C ratio parameters that occur both before and after the Jatikarya toll exit operates. The research method used is quantitative method by collecting road geometric data, geometric intersections and traffic data at present 2019 through direct surveys at the study site and related data on the Cimanggis - Cibitung toll road. From the research results, the average velocity value on Transyogi road is 23 km / hr and V / C ratio is = 0.9 during peak hours in existing conditions in 2019. Whereas after the toll road operates, the average speed value on Transyogi road is 32 km / hour and V / C constellation = 0.8 with the condition "do nothing". In "do something" conditions, namely with traffic management carried out mainly on intersections associated with Transyogi roads, namely intersection Kranggan, exit Jatikarya toll road, Ciangsana intersection and tourist city Exit Tol and obtained an average speed of 35 km / h and V / C ratio = 0.7. At 2029 , with "do something" conditions, namely with traffic management carried out mainly on intersections associated with Transyogi roads, namely four-way intersection of Kranggan, exit Jatikarya toll road, Ciangsana intersection and Kota Wisata exit Tol and obtained an average speed of 35 km / h and V/C ratio = 0.97